Social factors influencing females' decision to work abroad - Esmores, Jeannie Rose Joy
The study was conducted to determine the social factors that influence females' decision to work abroad. It seeks to find out the socio-demographic characteristics of the females who plan to work abraod, to find out whether those females who decide to work sbrosd have social networks in the country of destination and to fnd out their perceived employment, education and training opportunities in the country of destination. To reach the objectives of the study, interview schedule was used to gather necessary information from the randomly selected female respondents. Simple frequency counts were used in analyzing the data gathered. Results of teh study reveal that females who are likely to work abroad are between the ages 25-29 years old, majority are single, college graudates, and currrently unemployed, equally distributed to low, middle and high-income families and are middle children. Moreover, they also have social networks in the country of destination and feels that there are still other jobs available to them other than care giving. However, care giving was not viewed as a permanent job but passport to going abroad and stepping stone for a better job abroad. The countries preferred by the respondents are the wealthy countries which includes Canada, USA and the UK. These results demonstrate the importance of educational background and social networks in the country of destination, furthermore, the authors has found out that females who decide to work abroad feels that there are still jobs available for them other than care giving.